Collusion in the US generic drug industry - Robert Clark; Christopher Anthony Fabiilli; Laura Lasio (Queen's University, Department of Economics, 2021)
We study cartels that operated in the US generic drug industry, leveraging quarterly Medicaid data from 2011-2018 and a difference-in-differences approach comparing the evolution of prices of allegedly collusive drugs with a group of competitive control drugs. Our analysis highlights (i) the difficulty of establishing a suitable control group when collusion is pervasive, (ii) the importance of accounting for market structure changes when defining the control period, and (ii) the existence of across- and within-drug heterogeneity. We focus on six drug markets that that were part of the expanded initial complaint and where there was no entry in the same class during the collusive period, permitting a clean measure of the causal impact of collusion on prices. Our most conservative estimates suggest that collusion led to price increases of between 0% and 166% for each of the six drugs, and damages of between 0 and 3 million for the Medicaid market.
Keywords: L41; L12; L13; D22; D43; K21; I18; L65; 330; antitrust; generic drugs; price fixing